Pengaruh Arus Kas Terhadap Volume Perdagangan Saham Pada Perusahaan Manufaktur Bidang Industri Barang Konsumsi Di Bursa Efek Indonesia - -, SISKA SILVAYANTI (EKONOMIA, 2014)
Cash flow statement provides information about the cash inflows and cash outflows during the accounting period consists of cash flows arising from operating activities and used for, investing activities and financing activities. By looking at the statement of cash flows, the investor has a picture of the financial condition of the company, if the good cash flow, investors will be interested in buying shares in the company, so the demand for corporate stock are become greater which led to increased trading volume, otherwise if cash flow is not good, of course investors are reluctant to buy the company's shares and will tend to even sell the company's stock, so it will affect the volume of stock trading.        The problem is “Are operating cash flow, investing cash flow and financing cash flows in partially and simultaneously has significant effect to the volume of stock trading on companies manufacturing consumer goods industry in Indonesia Stock Exchange.        The purpose of this study was to determine whether the statement of cash flows will affect the investor in making an investment decision. Investor's decision is expected to be visible from the change in volume of stock trading.        The population of this research is the field of industrial manufacturing company listed consumer goods and cash flows reported in the Indonesian Stock Exchange during the period of 2009-2011. The sampling method used is Convenion Purpose Sampling. The total number of companies that meet the criteria of 29 companies from 36 samples. The results of this study stated that simultaneously cash flow from operating activities, cash flows from investing activities and cash flows from financing activities significantly influence the volume of stock trading on companies manufacturing consumer goods industry in Indonesia Stock Exchange. Partially, cash flow from operating activities significantly effect the stock trading volume, while cash flow from investing activities and cash flows from financing activities not significantly effect on the volume of trading stock in companies manufacturing consumer goods industry in Indonesia Stock Exchange